Neural sphingosine 1‐phosphate accumulation activates microglia and links impaired autophagy and inflammation. Issue 10 (24th June 2019) - Karunakaran, Indulekha; Alam, Shah; Jayagopi, Surendar; Frohberger, Stefan J.; Hansen, Jan N.; Kuehlwein, Janina; Hölbling, Benedikt V.; Schumak, Beatrix; Hübner, Marc P.; Gräler, Markus H.; Halle, Annett; van Echten‐Deckert, Gerhild
Abstract: Microglia mediated responses to neuronal damage in the form of neuroinflammation is a common thread propagating neuropathology. In this study, we investigated the microglial alterations occurring as a result of sphingosine 1‐phosphate (S1P) accumulation in neural cells. We evidenced increased microglial activation in the brains of neural S1P‐lyase (SGPL1) ablated mice (SGPL1 fl/fl/Nes ) as shown by an activated and deramified morphology and increased activation markers on microglia. In addition, an increase of pro‐inflammatory cytokines in sorted and primary cultured microglia generated from SGPL1 deficient mice was noticed. Further, we assessed autophagy, one of the major mechanisms in the brain that keeps inflammation in check. Indeed, microglial inflammation was accompanied by defective microglial autophagy in SGPL1 ablated mice. Rescuing autophagy by treatment with rapamycin was sufficient to decrease interleukin 6 (IL‐6) but not tumor necrosis factor (TNF) secretion in cultured microglia. Rapamycin mediated decrease of IL‐6 secretion suggests a particular mechanistic target of rapamycin (mTOR)‐IL‐6 link and appeared to be microglia specific. Using pharmacological inhibitors of the major receptors of S1P expressed in the microglia, we identified S1P receptor 2 (S1PR2) as the mediator of both impaired autophagy and proinflammatory effects. In line with these results, the addition of exogenous S1P to BV2 microglial cells showed similar effects as those observed in the genetic knock out of SGPL1 in the neural cells. In summary, we show a novel role of the S1P‐S1PR2 axis in the microglia of mice with neural‐targeted SGPL1 ablation and in BV2 microglial cell line exogenously treated with S1P. Main points: S1P secreted by SGPL1 deficient astrocytes activates microglia toward a proinflammatory phenotype. S1P ‐S1PR2 axis mediates microglial IL‐6 secretion and defective autophagy.